Stabilised control strategy for PEM fuel cell and supercapacitor propulsion system for a city bus. (5th July 2018) - Wu, W.; Partridge, J.S.; Bucknall, R.W.G.
Abstract: Fuel Cell (FC) buses have been developed as a long term zero emission solution for city transportation and have reached levels of maturity to supplement the coming London 2020 Ultra low emission zone implementation. This research developed a scaled laboratory Fuel Cell/Supercapacitor hybrid drivetrain implementing DC/DC converters to maintain the common busbar voltage and control the balance of power. A novel and simple hybrid control strategy based on balancing the currents on the common busbar whilst maintaining a stable FC output has been developed. It has been demonstrated that the FC power output can be controlled at a user defined value for both steady state and transient load conditions. The proposed control strategy holds the promise of extending FC life, downsizing power systems and improving the FC operating efficiency. Highlights: A laboratory Fuel Cell/Supercapacitor hybrid drivetrain has been constructed. A control strategy with a constant user defined Fuel Cell output has been designed. Proposed control strategy is evaluated under steady state and dynamic conditions. Advantages and limitations of the proposed control strategy have been analysed.